Efficacy and safety of macitentan for pulmonary hypertension: A meta‐analysis - Dan Du; Ya‐Dong Yuan (The Clinical Respiratory Journal, 2023)
Abstract Introduction Our purpose of this study is to evaluate the effect and safety of macitentan in the treatment of pulmonary hypertension (PH). Methods We retrieved the safety and efficacy of macitentan treatment for PH using PubMed, the Cochrane Library, EMBASE databases and clinicaltrials.gov. The Cochrane Risk of Bias Tool was used for literature screening and quality assessment. Data analysis was conducted using RevMan 5.4.1 and Stata/SE 15.1 software. Results are presented as standardization mean differences (SMDs) and odds ratio (OR). Results Meta‐analysis of seven randomized controlled trial (RCT) studies and four non‐RCT studies with 2769 patients was included, involving 723 in the macitentan group and 599 in the placebo group. The results of the study showed that macitentan had effectively decreased pulmonary vascular resistance (PVR) (SMD = −0.53, 95% CI: −0.77–−0.29, p < 0.05), cardiac index (CI) (SMD = 0.60, 95% CI: 0.37–0.83, p < 0.05) and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) (SMD = −0.22, 95% CI: −0.40–−0.03, p < 0.05). Furthermore, macitentan also significantly reduced PVR (SMD = −0.58, 95% CI: −0.80–−0.35, p < 0.05), 6‐min walk distance (6WMD) (SMD = 0.33, 95% CI: 0.15–0.50, p < 0.05), CI (SMD = 0.48, 95% CI: 0.28–0.69, p < 0.05), mean pulmonary arterial pressure (mPAP) (SMD = −0.43, 95% CI: −0.64–−0.23, p < 0.05) and NT‐proBNP (SMD = −0.55, 95% CI: −1.07–−0.03, p < 0.05) between baseline and follow‐up. The adverse reactions to macitentan were mild, with headache, anaemia and bronchitis. Other efficacy and safety outcomes did not reach statistical differences. Conclusion Macitentan therapy for PH is effective and safe. The effectiveness on PVR, mPAP, mean right atrial pressure (mRAP), mortality and other indicators still needs to be further confirmed.